Acetylcholinesterase (AChE) Biosensors for Determination of Carbamate Pesticides - Shafiquzzaman Siddiquee; Anwar Samsidar (Springer International Publishing, 2019)
Applications of nanotechnology are the remarkable sizes dependent on physiochemical properties of nanomaterials that have led to the developed protocols for synthesizing nanomaterials over a range of size, shapes and chemical compositions. Nanomaterials are normally powders composed of nanoparticles which exhibit properties that are different from powders. Nanotechnology is the engineering of functional systems at the molecular scale with their wide applications in energy sector, including -but not limited to- energy resources, energy conversion, energy storage, and energy usage; drug delivery systems including- safety concerns, perspective, challenges, target therapeutics for cancer, neurodegenerative diseases and other human diseases, nanomaterials based tissue engineering; and food sectors including to- food safety and quality, opportunities, challenges, nanomaterials based enhancing food packing, and determination of foodborne pathogens, agro and marine food, analysis of market, regulations and future prospects.